Torque Control Based Speed Synchronization for Two-Speed Gear Electric Vehicle - Taeyeon Lee (IEEE, 2021)
Two-speed gears are used to secure a wide torque-speed range while improving the power efficiency. In electric vehicles (EVs), a simple sleeve mechanism is preferred for gear shifting. This is because, during the speed synchronization process, the propulsion motor can adjust its speed for the new gear ratio. For such a purpose, speed controllers are commonly used. Since the torque control is the normal control mode in the vehicle, the control mode should be switched temporarily to the speed control for gear shift and turned back to the torque control mode. It is very onerous, and requires some setting time for each mode change. In this work, a synchronization method is established in the torque control mode. Furthermore, a recursive least squares (RLS) algorithm is utilized to estimate the vehicle parameters, based on which the vehicle speed variation is predicted during the shifting process. This method works satisfactorily on uphill, downhill, rough or smooth asphalt roads without changing the control mode. Experiments were performed on a wheel dynamo system, along with extensive simulation studies.